Filtration of simulated Martian atmosphere for in-situ oxygen production. (15th October 2020) - McClean, J.B.; Merrison, J.P.; Iversen, J.J.; Azimian, M.; Wiegmann, A.; Pike, W.T.; Hecht, M.H.; ,
Abstract: In-Situ Resource Utilisation (ISRU) can reduce the mass and cost of planetary missions. The Mars Oxygen ISRU Experiment (MOXIE) on the Mars 2020 rover Perseverance will demonstrate ISRU on Mars for the first time by producing oxygen from atmospheric carbon dioxide via solid oxide electrolysis. To protect the solid oxide electrolysis subsystem from contamination by dust, a High Efficiency Particulate Air (HEPA) filter is used. However, the performance of HEPA filters in Martian atmospheric conditions is not well understood. The theory of filtration was reviewed in the context of filtration of Mars' atmosphere, and an experimental investigation was carried out to determine the dust loading rate and pressure drop as a function of dust loading and filtration velocity for a flight-representative pleated and baffled MOXIE HEPA filter using wind tunnels and Martian dust simulant. In simulated atmospheric conditions of 10.3 ​mbar carbon dioxide at room temperature with a horizontal wind speed of 3 ​m ​s −1 and filter inlet face velocity of 7.1 ​cm ​s −1, the dust loading rate was (0.19 ± 0.02) mg ​m −2 h −1 . This is likely a lower bound: analytical approaches estimate dust loading rates of up to approximately 20 ​mg ​m −2 h −1 . The pressure drop Δ P (mbar) as a function of dust loading m (g ​m −2 ) and filtration velocity U F (cm ​s −1 ) was Δ P = a m + b U F, where a = 0.0012(1)mbar (g m -2 ) -1 (cm s -1 ) -1 and b = 0.063(1) mbar (cm s -1 ) -1 . Due to operation outside the continuum flow regime, pressure drop increased with atmospheric pressure, unlike HEPA filters on Earth where pressure drop is independent of atmospheric pressure. Dust is unlikely to produce a problematic pressure drop for MOXIE, but needs to be considered for large-scale filtration if the benefits of atmospheric ISRU on Mars are to be fully realised. Highlights: In-Situ Resource Utilisation (ISRU) can reduce mass and cost of planetary missions. The Mars Oxygen ISRU Experiment (MOXIE) will filter dust aerosol and produce oxygen. Analysis and experimental study of filtration of simulated Martian atmosphere. Determined filter dust loading as a function of time. Determined filter pressure drop as a function of dust loading.